حماية البيانات الشخصية في الإعلام الرقمي - فقيه، جيهان Faqih, Jihan (جامعة العربي بن مهيدي - أم البواقي, 2017)
This paper seeks, by presenting and analyzing, to shed the light on the right in personal privacy and the protection of personal data through social networks in light of the increase in the violation of the privacy of subscribers in social media networks according to the reports and statistics which appear every now and then. In fact, privacy is now subject to threats and personal data have become a vulnerable material used whether commercially or in marketing and advertisement, monitored by governmental agencies, or subjected to hacking and exploitation for harmful purposes to its owners.
تسعى هذه الورقة البحثية إلى تسليط الضوء بالطرح والتحليل على حقيقة حماية الحق في الخصوصية والبيانات الشخصية عبر مواقع التواصل الاجتماعي في ظل تنامي وتزايد ظاهرة انتهاك الخصوصيات الشخصية للمشتركين في مواقع التواصل الاجتماعي بحسب التقارير والإحصائيات التي تظهر بين الفينة والأخرى. حيث أصبحت الخصوصية مهددة وصارت البيانات الشخصية مادة يتم استخدامها إما تجارياً في تنفيذ دعاية تسويقية، أو مراقبتها من قِبل جهات حكومية، أو تعرضها للسرقة واستغلالها في أغراض تضر بأصحابها.
Keywords: الإعلام الرقمى -- الخصوصية المعلوماتية -- البيانات الشخصية -- مواقع التواصل الاجتماعى -- الإنترنت - قوانين وتشريعات